Effect of the frequency and temperature on the complex impedance spectroscopy (C-V and G-V) of p-ZnGa2Se4/n-Si nanostructure heterojunction diode - Yahia, I. S.; Fadel, M.; Sakr, G. B.; Shenouda, S. S.; Yakuphanoğlu, Fahrettin (Springer, 2012)
X-ray diffraction pattern and AFM results confirm the nanostructure of p-ZnGa2Se4/n-Si. The unit cell lattice parameters, the crystallite size L, the dislocation density delta, and the main internal strain epsilon were calculated. The temperature and frequency-dependent electrical characteristics of the Al/p-ZnGa2Se4/n-Si/Al heterojunction diode (HJD) have been investigated to determine the interface states which are responsible for the non-ideal behavior of the characteristics of the diode. The capacitance-voltage (C-V), conductance-voltage (G-V), and series resistance-voltage (R-s-V) characteristics of the diode have been analyzed in the frequency range of 5 kHz-1 MHz and temperature range of 303-423 K. The interfaces states of the diode were determined using conductance-voltage technique. The interface state density profile for the diode was obtained as a function of temperature and frequency. The values of the built-in potential V-bi, the doping concentration N-d and the barrier height phi(b(C-V)) of the diode were calculated at different temperatures and frequencies. Our experimental results revealed that both the series resistance and interface state density values must be taken into account in studying the impedance spectroscopy of HJD to stand up their performance for electronic applications characteristics.
Keywords: Schottky-Barrier Diodes; Nonlinear-Optical Properties; Interface States; Electrical Characteristics; Defect-Chalcopyrite; Series Resistance; Thin-Films; Sol-Gel; Capacitance; Semiconductor